2021
DOI: 10.1001/jamanetworkopen.2021.23616
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of Genotype-Specific Surveillance and Preventive Strategies for Gynecologic Cancers Among Women With Lynch Syndrome

Abstract: This economic evaluation analyzes the cost-effectiveness of screening and prevention strategies by genotype among women with Lynch syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 60 publications
(143 reference statements)
2
15
0
Order By: Relevance
“…Wright et al [ 52 ] evaluated the gene-specific cost-effectiveness of RRS in women with LS. They found that hysterectomy and ES at the age of 40 with DO at the age of 50 was an optimal strategy for MLH1 and MSH6 PV carriers, with ICURs of $33,269/QALY and $20,008/QALY, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al [ 52 ] evaluated the gene-specific cost-effectiveness of RRS in women with LS. They found that hysterectomy and ES at the age of 40 with DO at the age of 50 was an optimal strategy for MLH1 and MSH6 PV carriers, with ICURs of $33,269/QALY and $20,008/QALY, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For MSH2 PV carriers, the optimal strategy would be hysterectomy and ES at the age of 40 with DO at the age of 50, with utility scores for early menopause below 0.86, hysterectomy and BSO at the age of 40, with a utility score of 0.87–0.94, or hysterectomy and BSO at the age of 35, with a utility score greater than 0.95. If disutility of hysterectomy was taken into consideration, the optimal strategy would not change for MSH2 or MSH6 PV carriers, while hysterectomy and BSO at the age of 40 was favourable for MLH1 PV carriers; no intervention was optimal for PMS2 PV carriers, with a post-hysterectomy utility score less than 0.97 [ 52 ]. In PSA, the corresponding optimal strategy in the base case had a probability of 84.2% to be cost-effective for MLH1 , 71.0% for MSH6 , 86.2% for MSH2 and 91.6% for PMS2 .…”
Section: Resultsmentioning
confidence: 99%
“…Women with PMS2 pathogenic variants do not require BSO. While cost-effectiveness analysis of alternative strategies such as two-step surgery has been undertaken in Lynch Syndrome, there are no prospective trials evaluating this strategy and thus no available QOL outcomes [ 13 ]. Furthermore, women with PTEN pathogenic variants, a family history of EC, type 2 diabetes and/or obesity may benefit from RRH without BSO for increased EC (without OC) risk.…”
Section: Discussionmentioning
confidence: 99%
“…For women at substantially increased EC risk, such as those with Lynch syndrome, EC prevention is highly cost-effective for health systems [ 12 , 13 ] and recommended by international guidelines [ 14 ]. The most effective prevention is surgical removal of the uterus in the form of risk-reducing hysterectomy (RRH), which prevents 100% of EC cases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation